2017
DOI: 10.3847/1538-4357/aa8310
|View full text |Cite
|
Sign up to set email alerts
|

A Search for FRB 121102-like Persistent Radio-luminous Sources—Candidates and Implications for the FRB Rate and Searches

Abstract: The localization of the repeating fast radio burst (FRB), FRB 121102, suggests that it is associated with a persistent radio-luminous compact source in the FRB host galaxy. Using the FIRST radio catalog, I present a search for luminous persistent sources in nearby galaxies, with radio luminosities > 10% of the FRB 121102 persistent source luminosity. The galaxy sample contains about 30% of the total galaxy g-band luminosity within < 108 Mpc, in a footprint of 10,600 deg 2 . After rejecting sources likely due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…The dashed vertical curve marks t age for this model, for which the GHz band light-curve is near its peak. Additionally shown is data from the transient radio source J1419+3940 recently discovered by Law et al (2018) in a small star-forming galaxy with remarkably similar properties to the host of FRB 121102 (Ofek 2017). Although this event could represent the orphan radio afterglow of a long GRB, our modeling supplies some additional support for the magnetar nebula hypothesis.…”
Section: Resultssupporting
confidence: 74%
“…The dashed vertical curve marks t age for this model, for which the GHz band light-curve is near its peak. Additionally shown is data from the transient radio source J1419+3940 recently discovered by Law et al (2018) in a small star-forming galaxy with remarkably similar properties to the host of FRB 121102 (Ofek 2017). Although this event could represent the orphan radio afterglow of a long GRB, our modeling supplies some additional support for the magnetar nebula hypothesis.…”
Section: Resultssupporting
confidence: 74%
“…The first precise localization of an FRB revealed an unambiguous association with a luminous, persistent synchrotron radio source (Chatterjee et al 2017). Under the assumption that at least a subset of FRBs should have luminous persistent radio counterparts, Ofek (2017) identified 122 potential FRB hosts by identifying radio sources seen toward galaxies. In most cases, the radio sources are active galactic nuclei that reside in the centers of their host galaxies.…”
Section: Discoverymentioning
confidence: 99%
“…Based on the properties of FRB 121102's persistent radio source and host galaxy, Ofek (2017) identified a number of similar sources in the Very Large Array (VLA) FIRST catalogue. Law et al (2018) showed that one of these sources, FIRST J141918.9+394036 (hereafter FIRST J1419+3940) is a slowly declining transient.…”
Section: Introductionmentioning
confidence: 99%